Pests and Diseases Associated with Yam Bean (Pachyrhizus erosus) Cultivation at Farmers’ Levels in the Central Region of Benin - Rachidatou Sikirou; Bruno Zocli; Vincent Ezin; Adolphe Adjanonhoun; Kerstin Hell; Amoussatou Bouraïma; Sètondji Alban Paterne Etchiha Afoha; Léopold Simplice Gnancadja (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2020)
Roots and tubers are one of the most important crops that provide food security in West Africa. Thus, Pachyrhisus erosus with its various potentials, is planned to be introduced in Benin to improve the nutritional quality of the population. Prior to that, this study aimed at assessing pests and disease of P. erosus in the agroecological conditions in the central parts of Benin. Conducted at experimental field in Savè during two consecutive years, experiments were laid in a completely randomized block design with 4 replications and three treatments including EC 533 and EC Kew cultivars of P. erosus and cowpea variety named Kpodji-Guèguè. Results showed that the major pests collected from P. erosus namely Ootheca mutabilis, Medythia quaterna, Piezotrachelus varium, Megalurothrips sjostedti and Brevipalpus phoenis were not so far reported in it. Compared to cowpea, pest’s infestation and their damages were lower on P. erosus. Infestation severity on leaves and the percentage of perforated green pods ranged from 0.7% to 3% against 0.8% to 88.9% and from 12.5% to 16% against 57.2% to 64% respectively on P. erosus and cowpea. Cercospora disease caused by Cercospora canescens and yam bean leaf blight caused by an unknown fungus were observed. Cercospora disease affected cowpea and P. erosus while yam bean leaf blight affected only P. erosus. This study provides additional data on pests and diseases associated with P. erosus worldwide and alerts farmers regarding their management.